Hybridisation is associated with increased fecundity and size in invasive taxa: meta‐analytic support for the hybridisation‐invasion hypothesis. (19th September 2014) - Hovick, Stephen M.; Whitney, Kenneth D.; Gurevitch, Jessica
Abstract The hypothesis that interspecific hybridisation promotes invasiveness has received much recent attention, but tests of the hypothesis can suffer from important limitations. Here, we provide the first systematic review of studies experimentally testing the hybridisation‐invasion (H‐I) hypothesis in plants, animals and fungi. We identified 72 hybrid systems for which hybridisation has been putatively associated with invasiveness, weediness or range expansion. Within this group, 15 systems (comprising 34 studies) experimentally tested performance of hybrids vs. their parental species and met our other criteria. Both phylogenetic and non‐phylogenetic meta‐analyses demonstrated that wild hybrids were significantly more fecund and larger than their parental taxa, but did not differ in survival. Resynthesised hybrids (which typically represent earlier generations than do wild hybrids) did not consistently differ from parental species in fecundity, survival or size. Using meta‐regression, we found that fecundity increased (but survival decreased) with generation in resynthesised hybrids, suggesting that natural selection can play an important role in shaping hybrid performance – and thus invasiveness – over time. We conclude that the available evidence supports the H‐I hypothesis, with the caveat that our results are clearly driven by tests in plants, which are more numerous than tests in animals and fungi.